Determinants of repeated pregnancy among HIV-positive women on anti retroviral treatments at the public health facilities, in Gedeo zone, South Ethiopia: Unmatched case-control study - Yosef Lelamo; Atnafu Adem; Azmach Dache; Aregahegn Dona (Elsevier, 2022)
Background: The desire of HIV-infected woman to have children in the future has significant implications for the transmission of HIV to sexual partners and newborn. This study aimed to determine the determinants of repeated Pregnancy among HIV-positive women on Anti retroviral Treatments, at the public health facility, in Gedeo Zone, South Ethiopia. Methods: An unmatched case-control study was conducted from February 10 to April 27, 2020, among a total of 304 (76 cases and 228 controls) pregnant women. The participants were selected by randomly and data was collected using face-to-face interviewer-administered questionnaires, and entered using Epidata3.1 and analyzed by SPSS version 20. Bivariate logistic regression was used to select the candidate variables for the multivariable logistic regression with a p-value <0.25, and in the last multivariate logistic regression analysis was performed to assess determinant factors of repeated pregnancy in adjusted odds ratio with a p-value < 0.05, at 95% confidence level were declared statistically significant. Results: A total of 304 pregnant mothers responded resulting in a response rate of 97.4%. Determinants which were found to be associated with repeated pregnancy were history of abortion, low educational attainment, 30-43years of age, being employed, and urban residence. Conclusions: The results of the current study suggest that repeated pregnancies were more common among women who had a history of abortion and low educational attainment. Health practitioners of the Gedeo zone should give particular attention to prevent abortion and provide appropriate reproductive health services for those women.